7-Cyano-15-methoxy[6]helicene through a photochemical pathway and investigation of its chiroptical and photophysical properties - Hafedh, Nesrine; Asghar, Basim H.; Aloui, Faouzi (Comptes Rendus. Chimie, 2021)
7-Cyano-15-methoxy[6]helicene was synthesized, in 54% overall yield, through a short photochemical procedure including mild conditions and inexpensive reagents. The desired helical hexacyclic framework was characterized by $^{1}H$ and $^{13}C$ NMR and mass spectroscopies. Single crystals of the helicene were also obtained and an X-ray diffraction analysis is presented. Enantiomers of the helicene were obtained in 100% $ee$ after separation by chiral HPLC and their chiroptical properties were experimentally investigated from optical rotatory dispersion and electronic circular dichroism (ECD). UV–Vis absorption and fluorescence properties of the helicene were evaluated in solutions and a strong emission was noted in the blue region of the visible spectrum . Its electrochemical behavior was also experimentally examined and HOMO and LUMO energy levels were estimated, showing an electrochemical band gap of 2.11 eV. The results obtained herein are helpful to explain the interest of cyano and methoxy groups in making the new material a good candidate to be used in optoelectronic applications.